Pendampingan Implementasi Kurikulum Merdeka di SMA Muhammadiyah Mungkid Magelang - Ardiyarso Kurniawan; Christian Rudianto; Neny Isharyanti (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
The mentoring of Implementasi Kurikulum Merdeka is a program organized to support activities at Muhammadiyah Mungkid High School as a model school in creating a learning environment that is more dynamic, responsive and relevant to current developments and student needs so that it can produce graduates who are ready to face the demands of the world of work and life in the global era. Apart from that, this mentoring activity is proposed as additional independent mentoring provided through Sekolah Penggerak. This community service involved lecturers, students at Satya Wacana Christian University, and teachers at Muhammadiyah Mungkid High School, starting with differentiated learning and implementing Artificial Intelligence Chat GPT. This event was carried out for one day using the in-house training method. Based on the evaluation and feedback, this PkM activity had run effectively with practical activities in preparing class activities using differentiated learning and GPT Chat.